Analisis Implementasi dan Pengetahuan Ibu tentang PHBS Keluarga dengan Kejadian Diare pada Balita di Klinik Mitra Insani Kelurahan Gandasari Kota Tangerang Tahun 2022 - Tri Wahyuningsih; Masluroh Masluroh (Jurnal Keperawatan Muhammadiyah, 2023)
Background: Diarrhea predominantly attacks toddlers, toddlers' immune systems are still weak so toddlers are very vulnerable to the spread of causative organisms diarrhea. Diarrhea is one of the highest causes of death and morbidity in children, especially in toddlers.Objective: This study aims to analyze the implementation and knowledge of mothers on Family PHBS including proving the risk factors associated with the incidence of diarrhea in children under five at the Mitra Insani clinic, Gandasari Village, Tangerang City in 2022.Methods:This research is in the form of an observational analytic with a design approach cross-sectional study. The research was conducted using the statistical technique of chi-square test and regression to see the relationship between the dependent and independent variables. A sample of 56 people using simple random sampling method.Results: Implementation of Family PHBS in the environment around the Mitra Insani Clinic, Gandasari Subdistrict, Tangerang City in 2022 is relatively 60.7% less optimal in implementing family PHBS, Mother's knowledge of Family PHBS is relatively 58.9% of mothers have good knowledge, Diarrhea in Toddlers 71.4% are still in the high category. The result of the statistical test is the value of p = 1.000 p-value > 0.05 so that Ho is accepted and Ha is rejected. This shows that there is no significant relationship between mother's implementation of family PHBS and the incidence of diarrhea in toddlers, however, the OR value > 1 = 1.111 (0.337-3.665) shows that the implementation of toddler mothers in family PHBS is a risk factor for diarrhea in toddlers. Knowledge obtained p value = 0.773 p-value > 0.05 Ho is accepted and Ha is rejected. These results show that there is no significant relationship between mother's knowledge about PHBS and the incidence of diarrhea in toddlers, there is 1 factor that dominantly and significantly influences the incidence of diarrhea, namely the habit of boiling/sterilising formula milk bottles.Conclusion: Implementation of mothers in family PHBS is still not implemented, mother's knowledge of family PHBS is relatively good but the incidence of diarrhea is still relatively high. The test results show that implementation of mothers in family PHBS, mother's knowledge of family PHBS does not show a significant relationship to the incidence of toddler diarrhea. OR value > 1 = 1.111 (0.337-3.665) This shows the implementation of Mother Toddlers in Family PHBS is an adequate risk factor for diarrhea in toddlers. there is 1 dominant factor influencing the incidence of diarrhea, namely the habit of boiling/sterilising formula milk bottles